Profile of COVID-19 Patients at Arifin Achmad Hospital, Riau Province Between January 2021 and June 2021 - Syaf, Syarlidina; Adrianison, Adrianison; Simanjuntak, Arya Marganda (Respiratory Science, 2024)
Background: Coronavirus disease 2019 (COVID-19) is a disease caused by a new coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, previously called 2019 novel coronavirus) which was first identified in Wuhan City, Hubei Province, China. World Health Organization declared COVID-19 a global pandemic on March 12 2020 and until June 2021 there were 184 million cases with 3.9 million deaths worldwide. In Indonesia, until June 2021 there have been 2.2 million positive cases of COVID-19 and 60 thousand deaths. Method: The data collection method used in this study is a descriptive cross-sectional approach. According to the inclusion criteria, samples were collected for six months, and the results are shown as a distribution table. Results: The number of patients treated for the period from January to June 2021 totaled 1,442 people. The highest number of patients treated according to age was middle-aged (40.6%) and children (1.1%). The number of COVID-19 patients based on length of treatment from January to June was suspected (2-4 days) 28.13%, confirmed (5–45 days) 61.6%, discharged at own request 9.78%, referred 0.48%. The number of cured COVID-19 patients being treated at the Arifin Achmad Hospital in Riau Province from January to June 2021 has recovered 75.9% and died 13.7%. Conclusion: In Indonesia, until June 2021 there have been 2.2 million positive cases of COVID-19 and 60 thousand deaths. Riau Province as of June 2021 has recorded 70,520 confirmed cases and 1,931 deaths. The Arifin Achmad Pekanbaru General Hospital from March 2020 to June 2021 recorded 1,524 confirmed cases and 148 deaths.